Reflecting the Scenario of Earthquake (2015) Affected Communities in Historic Cities of Kathmandu Valley; Hassles or Delays? - Kawan, Shyam Sunder (SCITECH Nepal, 2020)
Along with the establishment of Nepal Reconstruction Authority (NRA) vigorous discussions in bringing attention of communities as major responsibility in heritage conservation had been done in relation to earthquake affected cultural heritage areas in 2015. Likewise, numbers of reconstruction projects had also been forwarded and are being undertaken at different levels of implementation by respective authorities. In a figurative interpretation, NRA is at the verge of completion of reconstruction works in substantial numbers. However, the process of reconstruction still remained ambiguous to the communities of major cultural heritage sites plundering to dilemmas in implementation, of which many are still in disputes. Apart from the monument reconstruction in these areas, reconstruction works of private heritages have plunged into a prime concern on economic development through tourism promos unlikely to keeping cultural heritage essence, while the latter seems awful in fulfilling their basic demands of livelihood. This paper assumes either of these deeds is rampant on the long run of heritage conservation major goals. Thus, it considers major 3 areas concentric to Kathmandu valley heritage sites i.e. Bungamati, Sankhu and Panga that are in the process of reconstruction and identify probable consequences brought over by ongoing enigmas among the communities and authorities in due course of reconstruction. It also seeks to assess them through the prism of authenticity criteria and sustainability measures of heritage assets based on community participation in reconstruction process. Ultimately, it highlights the necessity of instant and rapid reconstruction as well as conservation measures in Kathmandu valley by identifying the real owners, authorities and beneficiaries responsible for keeping intact the heritage resources.